An evaluation of juvenile delinquent rehabilitation in skill development program at Henry School,Melaka / Nur Adilah Abd Rahman - Abd Rahman, Nur Adilah (2015)
The concept of program effectiveness as a fundamental element in program evaluation is used to understand the extent of Skill Development Program (SDP) in correction institution of Henry Gurney School as a key player in the effectiveness of Juvenile Rehabilitation Program. The main objective of Henry Gurney School in SDP is to produce maximum possible skilled and semi-skilled among juveniles who have strong self-reliance after their release. Skill development is seen as the alternatives in restoring the confidence and intrinsic motivation to change for juveniles that can rejuvenate the hope to live in the community. Hence, meeting the interwoven skill development and nurturing self-reliance among trainees is vital to support this vulnerable group after their release. The study aims; i) to evaluate the Skills Development Program on trainee's reactions, learning adoption and behaviours; ii) to examine the extent of the program in achieving the program objective; and iii) to examine the trainees' perceptions about the current system of Skill Development Program with a view to contribute to the program's improvement. A qualitative approach is used in this study and had managed to interview ten trainees. This study confirms that Kirkpatrick's Theory & Model (1965) is used comprehensively in explaining the program evaluation of Skill Development. The relevant factors and themes that explain trainees' reactions, learning adoption and behaviours are identified. Parallel with the research objectives, findings show that i) there is a strong evidence that trainees were developing positive value in reactions, learning adoption and behaviours towards SDP; ii) SDP is achieved with the program objective in nurturing self-reliance among trainees; and iii) trainees' perceptions for program improvement are recommended for program distinction in courses offered and the need of family integration and social support is vital to support this group. This study contributes to the understanding of the current system in SDP based on the trainees' perspectives.